2008
DOI: 10.1111/j.1524-4741.2008.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Mastitis, Erythema Nodosum, and Oligoarthritis in a Pregnant Woman

Abstract: n Abstract: Granulomatous mastitis (GM) is an uncommon chronic inflammation of the breast and erythema nodosum (EN), is a rare extramammary manifestation of this entity. We describe a case of GM with EN and arthritis in a young pregnant woman. Review of literature showed rare similar cases. n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 20 publications
2
41
1
Order By: Relevance
“…In 1987, Adams et al reported the first case of granulomatous mastitis complicated by arthritis and erythema nodusum (2). Although cases of granulomatous mastitis complicated solely by erythema nodusum are occasionally reported, as far as we know, only two other cases of granulomatous mastitis complicated by both arthritis and erythema nodusum have been previously reported (3,4). Because granulomatous mastitis usually develops in association with lactation, hyperprolactinemia or breast injury, an immune response to extravasated secretions from lobules has been proposed as an underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1987, Adams et al reported the first case of granulomatous mastitis complicated by arthritis and erythema nodusum (2). Although cases of granulomatous mastitis complicated solely by erythema nodusum are occasionally reported, as far as we know, only two other cases of granulomatous mastitis complicated by both arthritis and erythema nodusum have been previously reported (3,4). Because granulomatous mastitis usually develops in association with lactation, hyperprolactinemia or breast injury, an immune response to extravasated secretions from lobules has been proposed as an underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Polyarthritis and erythema nodosum, as opposed to fever, are rare systemic manifestations of granulomatous mastitis. As far as we know, only three such cases have so far been reported (2)(3)(4).…”
Section: Introductionmentioning
confidence: 95%
“…Since a diagnosis by fine needle aspiration cytology (FNAC) is now commonplace for all types of processes in various organs, including the breast, it is felt that the findings in GM can be reliably diagnosed by the least invasive method of FNAC, which has been described in only a few reported cases of GM. 7,[9][10][11] We present our total experience with 18 cases of GM that were diagnosed by FNAC in a period of 27 years from > 40,000 fine needle aspirations of the breast since FNAC became an integral part of investigation protocol in our practice.…”
Section: The Ages Of the Women Ranged From 28 To 38 Years With A Meamentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Two of these reports were associated with pregnancy and lesions had appeared in third trimester. 4,5 Arthritis accompanying IGM regresses concurrently with resolution of IGM, which suggests that arthritis in these cases was the result of a reactive process. 6,8,10 Mild IGM usually resolves spontaneously with drainage.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been rarely associated with oligoarthritis and erythema nodosum (EN) in the literature. [4][5][6][7][8][9][10] In this article, we discuss the diagnostic, clinical, and therapeutic approach to a unique case with granulomatous mastitis, EN, and arthritis that may be of interest to clinicians who are not readily familiar with this condition.…”
mentioning
confidence: 99%